(untitled) (Scientific journal of the Fergana State University, 2023)
The macro- and microelement composition of the Physalis alkekengi plant was studied by mass spectrometry with inductively coupled argon plasma. It is shown that the plant contains a large number of macro- and microelements that are useful for a living organism.